2022
DOI: 10.1002/jeab.756
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age differences in approach behavior toward a port that delivers nicotine vapor

Abstract: The goal of our laboratory is to study the mechanisms that promote nicotine use, particularly in vulnerable populations. To more closely mimic human use patterns, the present study employed nicotine vapor methods involving passive exposure for 14 days in adolescent and adult female and male rats. Age and sex differences in approach behavior (nosepokes) were assessed in a port that delivered nicotine plumes on Day 1 and 14 of our exposure regimen. Controls received ambient air in exposure chambers. After the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The vapor inhalation model for delivery of nicotine to rat subjects is still relatively new with relatively few data available regarding plasma levels of nicotine, or the metabolite cotinine, across rat age, sex and strain. In one recent report, Espinoza and colleagues (Espinoza et al, 2022) found that Wistar rats exposed to 14 days of nicotine vapor (generated from 12 mg/mL in a vegetable glycerin / propylene glycol vehicle) for 90 minutes each day during the adolescent interval (PND 33-46) exhibited more nosepokes in the nicotine vapor delivery port during this passive drug delivery than did air-exposed control groups. Serum cotinine levels of ∼190-220 ng/mL were reported in all three groups other than female adolescents which were significantly higher (∼380 ng/mL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vapor inhalation model for delivery of nicotine to rat subjects is still relatively new with relatively few data available regarding plasma levels of nicotine, or the metabolite cotinine, across rat age, sex and strain. In one recent report, Espinoza and colleagues (Espinoza et al, 2022) found that Wistar rats exposed to 14 days of nicotine vapor (generated from 12 mg/mL in a vegetable glycerin / propylene glycol vehicle) for 90 minutes each day during the adolescent interval (PND 33-46) exhibited more nosepokes in the nicotine vapor delivery port during this passive drug delivery than did air-exposed control groups. Serum cotinine levels of ∼190-220 ng/mL were reported in all three groups other than female adolescents which were significantly higher (∼380 ng/mL).…”
Section: Introductionmentioning
confidence: 99%
“…To the end of directly comparing nicotine distribution and cotinine generation across sex and two common rat strains, within a single lab model, we first conducted a study of plasma concentrations of nicotine and cotinine after vapor exposure and after subcutaneous injection. This is particularly critical since methods related to vapor puffing protocols, session duration, and rat strain have varied across this emerging literature (Espinoza et al, 2022; Javadi-Paydar et al, 2019b; Montanari et al, 2020). Similarly, the behavioral and physiological effects of vapor inhalation of nicotine have not yet been reported for adolescent rats, so we next determined if effects on locomotor activity and thermoregulation previously reported in adult animals (Javadi-Paydar et al, 2019b) would generalize to adolescents of each sex.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to embracing cultural responsiveness in behavior‐analytic research is to allow the methodology to fit the question by moving beyond single‐case research designs. Although basic behavior analysis researchers have embraced methodologies beyond single‐case research designs (e.g., group designs; Espinoza et al, 2022), there are research methods that can further advance DEIA efforts. For example, community‐based participatory research (Hacker, 2013) is a collaborative approach to research in which researchers and community partners work together throughout the entire research process with the goal of enhancing the ability to address issues that are important to the community in a sustainable and influential manner.…”
Section: Research Questions and Methods Employedmentioning
confidence: 99%
“…Indeed, this new model may have especially strong translational validity for PTE as well as vaping given similar pharmacokinetics. Several labs have now started to use vapour models of nicotine intake and we hope to see more studies of this type in the future (Smith et al, 2020;Cooper et al, 2021;Henderson and Cooper, 2021;Lallai et al, 2021;Patten et al, 2021;Ruffolo et al, 2021;Espinoza et al, 2022).…”
Section: Future Directionsmentioning
confidence: 99%